2012
DOI: 10.1002/eji.201142011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced structural stability of Concholepas hemocyanin increases its immunogenicity and maintains its non‐specific immunostimulatory effects

Abstract: Hemocyanins, which boost the immune system of mammals, have been used as carrieradjuvants to promote Ab production against haptens and peptides, as immunostimulants during therapy for bladder carcinoma and as a component in therapeutic vaccines for cancer. These biomedical applications have led to growing interest in obtaining hemocyanins with high immunogenicity. Here, we study the immunological properties of a modified oxidized Concholepas concholepas hemocyanin (Ox-CCH) obtained by the oxidation of its carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 62 publications
2
54
0
1
Order By: Relevance
“…2B). Therefore, these results strongly suggest that the slow Ag processing in macrophages, which also occurs in DCs (8,14), allows the sequestration of these proteins for presentation to T lymphocytes several days later, which is a key feature of Ags that enhance immunogenicity (45).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…2B). Therefore, these results strongly suggest that the slow Ag processing in macrophages, which also occurs in DCs (8,14), allows the sequestration of these proteins for presentation to T lymphocytes several days later, which is a key feature of Ags that enhance immunogenicity (45).…”
Section: Resultsmentioning
confidence: 85%
“…However, the response was sufficient to induce the secretion of several proinflammatory cytokines, including IL-6, IL-12p40, IL-23, and TNF-a (58). It has been shown that the lysosomal activity in DCs is less efficient in macrophages (59), and this activity cannot significantly degrade large proteins (60), such as KLH or CCH (14). It is unlikely that these structures hydrolyze these proteins to smaller peptide fragments equivalent to those found in macrophages (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations